Current status of thulium fibre laser lithotripsy: an up‐to‐date review. (2nd August 2021) - Jones, Patrick; Beisland, Christian; Ulvik, Øyvind
Abstract : Objective: To perform an up‐to‐date review to scope the current status of the thulium fibre laser (TFL) in the setting of stone lithotripsy and provide a guide for the clinical urologist. Methods: A review of world literature was performed to identify original articles on TFL for stone lithotripsy. Our clinical experiences of using the technology have also been shared. Results: To date there have been 11 clinical studies published on TFL for stone lithotripsy. Three of these have been in the setting of miniaturised percutaneous nephrolithotomy (mini‐PCNL) and the remainder have been on ureteroscopy (URS). There has only been one randomised study on this technology, which has been for URS. For URS, the range of settings has been 0.1–4 J × 7–300 Hz for both URS and mini‐PCNL. Stones ranging from 0.4–3.2 and 1.5–3 cm have been treated with URS and mini‐PCNL, respectively. The final stone‐free rate for TFL has ranged from 66.6% to 100% and 85–100% for URS and mini‐PCNL, respectively. The average length of stay ranged from 0.5 to 2.4 days in the URS group, but no studies have been reported this for mini‐PCNL. Operative times in all the studies (both URS and mini PCNL) were <60 min. Conclusion: Initial clinical studies reveal that TFL appears to be efficacious in the setting of stone lithotripsy. However, further randomised trials are warranted to delineate its formal position, as well as determine the optimal settings for use in clinical practice.